Rapid-response radio observations of short GRB 181123B with the Australia Telescope Compact Array. Issue 3 (13th March 2021) - Anderson, G E; Bell, M E; Stevens, J; Aksulu, M D; Miller-Jones, J C A; van der Horst, A J; Wijers, R A M J; Rowlinson, A; Bahramian, A; Hancock, P J; Macquart, J-P; Ryder, S D; et al.
ABSTRACT: We introduce the Australia Telescope Compact Array (ATCA) rapid-response mode by presenting the first successful trigger on the short-duration gamma-ray burst (GRB) 181123B. Early-time radio observations of short GRBs may provide vital insights into the radio afterglow properties of Advanced LIGO- and Virgo-detected gravitational wave events, which will in turn inform follow-up strategies to search for counterparts within their large positional uncertainties. The ATCA was on target within 12.6 h post-burst, when the source had risen above the horizon. While no radio afterglow was detected during the 8.3 h observation, we obtained force-fitted flux densities of 7 ± 12 and 15 ± 11 μ Jy at 5.5 and 9 GHz, respectively. Afterglow modelling of GRB 181123B showed that the addition of the ATCA force-fitted radio flux densities to the Swift X-ray Telescope detections provided more stringent constraints on the fraction of thermal energy in the electrons (log ε _e = -0.75^+0.39_-0.40 rather than log ε _e = -1.13^+0.82_-1.2 derived without the inclusion of the ATCA values), which is consistent with the range of typical ϵ e derived from GRB afterglow modelling. This allowed us to predict that the forward shock may have peaked in the radio band ∼10 d post-burst, producing detectable radio emission ≳3–4 d post-burst. Overall, we demonstrate the potential for extremely rapid radio follow-up of transients and the importance of triggered radio observations for constraining GRB blast wave properties, regardless of whether there is a detection, via the inclusion of force-fitted radio flux densities in afterglow modelling efforts.